Wheat Improvement, Management and Utilization 2017
DOI: 10.5772/67271
|View full text |Cite
|
Sign up to set email alerts
|

Wheat in Kenya: Past and Twenty-First Century Breeding

Abstract: Plant breeders aim to improve crop varieties to benefit humankind. Since wheat was introduced in Kenya, numerous varieties have been released and cultivated to varying extents. Past genetic gains have been fragile due to various environmental challenges-mostly rust diseases, and unfavorable socio-economic national policy for the crop. The role and the contribution of wheat breeding to the success of the crop in Kenya for over a century is reviewed. It is considered that systematic exploitation of local and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…It is not exactly clear why the Rht-B1b allele was preferentially selected instead of Rht-D1b allele given that both alleles have similar effect on plant height and grain size. It is worth noting, however, that majority of the EA wheat varieties released post-1970 are introductions from international wheat breeding programs including CIMMYT and ICARDA (Macharia and Ngina 2017). In agreement with our result, Zhao et al (2019) showed a higher percentage of the Rht-B1b allele in CIMMYT germplasm compared to the Rht-D1b allele.…”
Section: Allele Frequency Changes Across Breeding Periods and Balancisupporting
confidence: 92%
“…It is not exactly clear why the Rht-B1b allele was preferentially selected instead of Rht-D1b allele given that both alleles have similar effect on plant height and grain size. It is worth noting, however, that majority of the EA wheat varieties released post-1970 are introductions from international wheat breeding programs including CIMMYT and ICARDA (Macharia and Ngina 2017). In agreement with our result, Zhao et al (2019) showed a higher percentage of the Rht-B1b allele in CIMMYT germplasm compared to the Rht-D1b allele.…”
Section: Allele Frequency Changes Across Breeding Periods and Balancisupporting
confidence: 92%
“…Wheat demand has been growing at an average of about 4% per annum [3] driven by an upswing population, booming incomes, and rural-urban migration [4]. changing preferences to wheat-based diets associated with urbanization has been a significant factor driving wheat demand upward [5].…”
Section: Introductionmentioning
confidence: 99%
“…Limited water availability is a major issue for wheat production around the world [ 2 ]. Approximately 45% of the wheat-growing lands in developing countries are vulnerable to drought [ 3 ]. The situation of wheat production may become more problematic since the area affected by the drought stress may increase four times by the middle of the 21st century [ 4 ].…”
Section: Introductionmentioning
confidence: 99%